Effects of stachyose on gut microbiota and metabolic pathways in children with diarrhea - Bing WANG; Hui JIN; Xiong'e PI; Yan WU; Weiran WANG; Wei LIU; Gang ZHAO (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the effects of stachyose on the structural composition and metabolic pathways of gut microbiota in children with diarrhea using metagenomic sequencing technology. MethodsSix stool samples were collected from children with diarrhea admitted to a tertiary hospital from December 2021 to March 2022 using the direct selection method. The samples were inoculated into stachyose medium (STS group) and control medium (Ctrl group) using in vitro simulated fermentation technology. Fecal genomic DNA was extracted, and the effects of stachyose on the composition and diversity of gut microbiota were analyzed through metagenomic sequencing. At the COG and KEGG metabolic function levels, PCoA analysis was performed to determine the contribution of dominant gut microbiota to KEGG functional pathways, and the correlations between metabolites and gut microbiota and KEGG metabolic pathways were analyzed. ResultsAlpha diversity analysis showed that except for the Simpson index (0.29, 0.24, P < 0.05), the differences in the Ace index (143.17, 127.00), Chao index (143.17, 127.00), and Shannon index (1.69, 1.79) between the STS and Ctrl groups were not statistically significant. The relative abundances of Bifidobacterium longum (0.06%), Ruminococcus (0.05%), and Lactobacillus salivarius (0.04%) were higher in the STS group than in the Ctrl group. PCoA analysis at the COG and KEGG metabolic function levels revealed that the differences between the two groups were statistically significant (P < 0.05). The STS group upregulated characteristic metabolic pathways such as purine metabolism, starch and sucrose metabolism, and galactose metabolism while downregulating the characteristic metabolic pathways of the Ctrl group. Compared with the Ctrl group, the increased abundance of microbiota in the STS group showed high contributions to metabolic functions related to KEGG level 3. Spearman's correlation coefficient analysis found close associations between metabolic products of gut microbiota and related gut microbiota and KEGG metabolic pathways. ConclusionStachyose can regulate the structural composition of gut microbiota in children with diarrhea, increase gut microbiota diversity, promote related metabolic functions, and produce more beneficial substances for the human body.